Pediatric Surgery A Quick Guide to Decision-making - Choudhury, Subhasis Roy (Springer Singapore, 2018)
This book covers all the common surgical diseases affecting children, reflecting the latest available information. In addition, it discusses recent advances in pediatric surgery, including fetal interventions and minimally invasive surgery. The text is presented in a concise and reader-friendly style and complemented by numerous photographs and illustrations to aid in comprehension. Each chapter is structured in a systematic uniform pattern, examining the embryology, incidence, and approach to diagnosis and management, along with flow charts and algorithms where appropriate. The book is primarily intended for fellows-in-training and surgeons in pediatric surgery and pediatric specialties. In addition to familiarizing readers with common pediatric surgical conditions and helping them plan simple approaches to their management, it also offers an essential on-the-go guide. .